The Effect of Thermal and Alkaline Pretreatment in POME (Palm Oil Mill Effluent) as a Substrate for Dark Fermentation Process on Biohydrogen Production - Amna Citra Farhani; Bintang Sipartogi Panjaitan; Ni Wayan Arya Utari (The University of Lampung, 2026)
Palm Oil Mill Effluent (POME) is a promising substrate for biohydrogen production through dark fermentation, although pretreatment is often required to enhance hydrogenogenic activity. This study evaluated the effects of alkaline (NaOH) and thermal pretreatments on POME characteristics and hydrogen production. Fresh POME was sieved and adjusted to initial pH values of 6, 7, or 8 using 6 M NaOH, with or without heat shock treatment (100 °C for 60 min). Batch fermentation was conducted at 60 °C for 24 h, while pH, oxidation-reduction potential (ORP), and dissolved oxygen (DO) were monitored. Pretreatment shifted POME conditions from acidic and oxidative to neutral-alkaline and reductive environments, with several treatments achieving ORP values below −200 mV, indicating favorable anaerobic conditions. Refrigerated storage reduced pH and increased ORP, whereas NaOH addition increased pH and lowered ORP. Hydrogen production varied among treatments. The highest yield was obtained from fresh POME adjusted to pH 7, producing 0.03655 g H₂ with an ORP of approximately −514 mV. In contrast, stored POME subjected to pH 7 adjustment and heat shock produced substantially lower hydrogen yields. In a second batch, pH 8 treatments generated 0.01157–0.02002 g H₂, representing 2.4–3.1 times higher production than the controls, while pH 6 treatments showed the lowest yields. Overall, neutral-to-alkaline pH and strongly negative ORP were associated with improved biohydrogen production.